Efficacy of application of a patient-specific implants in treatment of the orbit walls defects, combined with a cheekbone complex fractures - Yu. V. Chepurniy; A. V. Kopchak; D. M. Chernogorskiy; O. I. Zhukovtseva (Клінічна хірургія, 2020)
Objective. To study a clinical efficacy of application of a patient-specific implants for elimination of posttraumatic orbital defects, combined with a cheekbone complex fractures, comparing with standard methods of reconstruction.